Danni the drum fairy - Meadows, Daisy (New York : Scholastic, 2008)
Rachel and Kirsty try to keep Fairyland in harmony by capturing the goblin who has stolen the drum fairy's instrument.
4.7
K-3
Keywords: Fairies -- Juvenile fiction; Lost articles -- Juvenile fiction; Musical instruments -- Juvenile fiction; Fairies -- Fiction; Lost and found possessions -- Fiction; Musical instruments -- Fiction; Fantasy; Fairies -- Fiction; Lost and found possessions -- Fiction; Musical instruments -- Fiction; Fantasy fiction; Fairies -- Fiction; Drum -- Fiction; Music -- Fiction; Fantasy; Fantasy fiction